Study of endothelial nitric oxide, through saliva, in practitioners of different modalities of physical exercise - Agricola, Nestor Persio Alvim (2024)
In the present study, two parameters were evaluated: endothelial nitric oxide (NO), expressed in saliva as nitrite, and training intensity, by heart rate. The physical exercise modalities studied were: jump, weight training, crossfit, water aerobics, pilates and spinning. All data were compared to a control condition. The objective was to analyze the behavior of NO in different modalities of physical exercise. NO production responds to the exercise stimulus and is expressed in saliva, as verified in the repeated measures test comparing the four sample collections (p-value 0.027) and in the comparison with the control group (p-value 0.0032). The most intense exercise modalities present higher expression of post-exercise NO. However, the expression is not lasting, returning to baseline values ​​30 minutes after training. The nitric oxide synthesized varies according to the intensity of the exercise, that is, according to the greater blood flow. Some less intense forms of exercise are not able to potentiate the production of endothelial NO, a minimum intensity is required that will activate eNOS and the entire cycle of nitric oxide production.